EFFECTS OF MODIFIED ULTRAFILTRATION ON BLOOD PRODUCTS REQUIREMENT IN CHILDREN UNDERGOING OPEN HEART SURGERY - Tariq, Muhammad; Musaddiq, Yasmin; Naqvi, Shahab; Novick, William M.; Qayyum, Mazhar (Pakistan Armed Forces Medical Journal, 2018)
Objective: To find out the effects of modified ultrafiltration on blood products requirement for transfusion in congenital heart disease children after open heart surgery. Design: This was a quasi-experimental study between two clinical groups. Patients were assigned to both groups by using convenient sampling; to do Modified Ultrafiltration or not was surgeon’s preference who was unaware whether the patient is participating in any study or not. Place and Duration of Study: The study was carried out at Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD) Rawalpindi between August, 2005 and September, 2006. Patients and Methods: Total 200 patients were included in this study and were divided equally into two groups; study group (MUF) and control group (non MUF) keeping hundred patients in each group. Results: Significantly increased level of hemoglobin after MUF (9.7±1.4 gm/dl before MUF versus 13.6±1.6 gm/dl after MUF, p<0.001) and significantly decreased volume of blood products required for transfusion in study group (24.1±24.5 ml/kg versus control: 43.81±42.4 ml/kg, p<0.001). Significantly increased hemoglobin level was observed during first three days of ICU stay (12.6±1.8 g/dl versus control: 11.6±2.1 g/dl, p=0.001on first postoperative day ,11.3±1.8 g/dl versus control: 10.8±1.9 g/dl, p=0.039 on second postoperative day and 11.3±1.5 g/dl versus control: 10.5±1.8 g/dl, p=0.022 on third postoperative day). Conclusion: From this study we concluded that use of MUF is well tolerated in all the patients and due to removal of extra water from patients circulation after separation from CPB resulted in hemodynamic benefits, significantly less use of blood products and better postoperative hemoglobin and hematocrit management.